Handbook of transport modelling - Hensher, David A., 1947-; Button, Kenneth, 1948- (Bingley, U.K. : Emerald, 2007)
Since 2000, there has been an exponential amount of research completed in the field of transport modelling thereby creating a need for an expanded and revised edition of this book. National transport models have taken on the new modelling methods and there have been theoretical and empirical advances in performance measurement. Coverage will include current demand methods, data issues, valuation, cost and performance, and updated traffic models. Supplementary case studies will illustrate how modelling can be applied to the study of the different transport modes and the infrastructures that support them.The second edition of this handbook will continue to be an essential reference for researchers and practitioners in the field. All contributions are by leading experts in their fields and there is extensive cross-referencing of subject matter. This book features expanded coverage on emerging trends and updated case studies. It addresses models for specific applications (i.e., parking, national traffic forecasting, public transport, urban freight movements, and logistics management).
Modelling signalized and unsignalized junctions / Rod Troutbeck -- Trip timing / Mahmassani Hani S. -- Modelling parking / William Young -- National models / Andrew Daly, Pattarathep Sillaparchan -- An introduction to the valuation of travel time-savings and losses / Hugh F. Gunn, Pattarathep Sillaparcharn -- Can telecommunications help solve transportation problems? A decade later : are the prospects any better? / Ilan Soloman, Patricia L. Mokhtarian -- Automobile demand and type choice / David S. Bunch, Belinda Chen -- Modelling response to information systems and other intelligent transport system innovations / Peter Bonsall -- Frequency-based transit-assignment models / Joaqui<U+0301>n de Cea, Enrique Ferna<U+0301>ndez -- Models for public transport demand and benefit assessments / Kjell Jansson ... [et al.] -- Strategic freight network planning models and dynamic oligopolistic urban freight networks / Terry L. Friesz, Changhyun Kwon -- Urban freight movement modeling / Glen D'Este -- Value of freight travel-time savings / Gerard de Jong -- Modelling performance : rail / Chris Nash, Andrew Smith -- The performance of bus-transit operators / Bruno de Borger, Kristiaan Kerstens -- Models of airport performance / Peter Forsyth -- Modeling cost competitiveness : an application to the major North American airlines / Tae Hoon Oum, Chunyan Yu, Z.F. Li Michael -- Highway performance / Paul Rouse, Martin Putterill, Z.F. Li Michael -- Structure and operations in the liner shipping industry / H.E. Haralambides.
Includes indexes.
Print version record
Keywords: Transportation -- General; Business & Economics -- Industries -- Transportation; Transport industries; Transportation -- Planning -- Mathematical models